Electrochemical and optical-based immunosensor for detection of Mycobacterium tuberculosis - Mohd Bakhori, Noremylia (2019)
Tuberculosis (TB) caused by Mycobacterium tuberculosis is a major obstacle for the global that effect the rate of morbidity and mortality. Many attempts and affords had been taken such as developing the drugs for controlling TB, curing the patients and preventing further transmission of the disease. Conventional diagnosis tool of TB often time-consuming, required loads of samples, less sensitive, impractical and costly for point of care diagnostic. In this research, a novel for diagnosis of TB was developed by an optical and electrochemical immunosensor via antibody-antigen interaction for the detection of TB-protein biomarker CFP10-ESAT6. For optical immunosensor, we studied a naked eye detection for TB by utilizing plasmonic enzyme-linked immunosorbent assay (ELISA) for the detection of protein biomarker, Mycobacterium tuberculosis ESAT-6-like protein esxB (CFP10-ESAT6). Here, the biocatalytic cycle of the intracellular enzymes,catalase links to the formation and successive growth of the gold nanoparticles (AuNPs). The formation of blue and red of AuNPs colored solutions links directly to the absence or presence of the TB analytes in the sample solutions. The immunoassay involves catalase-labeled antibodies which consume hydrogen peroxide for reduction of gold (III) chloride and further produce AuNPs. The fast rate of reaction determines the agglomerated of AuNPs for blue solutions while slow reaction for red solution which from monodispersed AuNPs. This serves as a conﬁrmation for the naked eye detection of TB analytes. The optimum concentration of H2O2 and gold ion were 150 µM and 0.25 mM respectively. In the presence of CFP10-ESAT6, blue color produced while in the absence of CFP10-ESAT6, red solution appeared. The detection limit (LOD) of- developed method was 0.01 µg/mL by the naked eye. Additionally, the plasmonic ELISA shows high specificity towards CFP10-ESAT6 protein compared with MPT64 and BSA. Furthermore, our developed technique was successfully tested and conﬁrmed with sputum samples from patients diagnosed with positive and negative TB with good reproducibility. The results show only positive TB sputum samples produced blue color solutions compared with negative sputum samples, non-tuberculosis Runyon Group IV and Mycobacterium fortuitum chelonae complex. The results provided enough evidence for the utilization of our technique in the early diagnosis of TB disease.